Desensitization in delayed drug hypersensitivity reactions – an EAACI position paper of the Drug Allergy Interest Group. Issue 7 (7th June 2013) - Scherer, K.; Brockow, K.; Aberer, W.; Gooi, J. H. C.; Demoly, P.; Romano, A.; Schnyder, B.; Whitaker, P.; Cernadas, J. S. R.; Bircher, A. J.; ,
Abstract Drug hypersensitivity may deprive patients of drug therapy, and occasionally no effective alternative treatment is available. Successful desensitization has been well documented in delayed drug hypersensitivity reactions. In certain situations, such as sulfonamide hypersensitivity in HIV‐positive patients or hypersensitivity to antibiotics in patients with cystic fibrosis, published success rates reach 80%, and this procedure appears helpful for the patient management. A state of clinical tolerance may be achieved by the administration of increasing doses of the previously offending drug. However, in most cases, a pre‐existent sensitization has not been proven by positive skin tests. Successful re‐administration may have occurred in nonsensitized patients. A better understanding of the underlying mechanisms of desensitization is needed. Currently, desensitization in delayed hypersensitivity reactions is restricted to mild, uncomplicated exanthems and fixed drug eruptions. The published success rates vary depending on clinical manifestations, drugs, and applied protocols. Slower protocols tend to be more effective than rush protocols; however, underreporting of unsuccessful procedures is very probable. The decision to desensitize a patient must always be made on an individual basis, balancing risks and benefits. This paper reviews the literature and presents the expert experience of the Drug Hypersensitivity Interest Group of the European Academy of Allergy and Clinical Immunology.